A step ahead: Exploring the gut microbiota in inpatients with bipolar disorder during a depressive episode. (26th July 2018) - Painold, Annamaria; Mörkl, Sabrina; Kashofer, Karl; Halwachs, Bettina; Dalkner, Nina; Bengesser, Susanne; Birner, Armin; Fellendorf, Frederike; Platzer, Martina; Queissner, Robert; Schütze, Gregor; Schwarz, Markus J.; et al.
Abstract: Objectives: There is evidence that the gut microbiota plays a major role in the pathogenesis of diseases of the central nervous system through the gut–brain axis. The aim of the present study was to analyze gut microbiota composition in bipolar disorder (BD) and its relation to inflammation, serum lipids, oxidative stress, tryptophan (TRP)/kynurenine (KYN) levels, anthropometric measurements and parameters of metabolic syndrome. Further, microbial community differences of individuals with BD compared with healthy controls (HC) were explored. Methods: In this cross‐sectional study, we performed 16S rRNA gene sequencing of stool samples from 32 BD individuals and 10 HC. Laboratory parameters included inflammatory markers, serum lipids, KYN, oxidative stress and anthropometric measures. Microbial community analysis and correlation to clinical parameters was performed with QIIME, differential abundance analysis of taxa encompassed linear discriminant analysis effect size (LEfSe). Results: We found a negative correlation between microbial alpha‐diversity and illness duration in BD ( R = −0.408, P = 0.021). Furthermore, we identified bacterial clades associated with inflammatory status, serum lipids, TRP, depressive symptoms, oxidative stress, anthropometrics and metabolic syndrome in individuals with BD. LEfSe identified the phylum Actinobacteria (LDA= 4.82, P = 0.007) and the class Coriobacteria (LDA= 4.75, P = 0.010) as significantly more abundant in BD when compared with HC, and Ruminococcaceae (LDA= 4.59, P = 0.018) and Faecalibacterium (LDA= 4.09, P = 0.039) as more abundant in HC when compared with BD. Conclusions: The present findings suggest that causes and/or consequences of BD may also lie outside the brain. Exploratory research of the gut microbiota in affective disorders like BD may identify previously unknown underlying causes, and offer new research and therapeutic approaches to mood disorders.